Management of colorectal large cell neuroendocrine carcinoma: case report and literature review - Coelho, Marcio B.; Kovacs, Thomas M.; Stephensen, Bree D. (International Surgery Journal, 2024)
Large cell neuroendocrine carcinoma (LCNEC) of the colorectum is a rare, aggressive subtype of neuroendocrine cancer with a dismal prognosis. Accounting for a mere 0.25% of colorectal cancers, LCNEC is associated with a median overall survival of 4 to 16 months, and nearly all patients succumb within a year. Pure colorectal LCNEC reports are scarce, and this review and case study presents a 40-year-old male, the youngest reported patient, diagnosed with rectal LCNEC. A comprehensive PubMed search for “large cell neuroendocrine carcinoma” and “colorectal” was conducted. Titles were meticulously screened for relevance to the nuanced management of colorectal LCNEC. Despite aggressive therapeutic interventions, including chemotherapy with carboplatin and etoposide, the patient experienced rapid disease progression, emphasizing the challenging nature of LCNEC. The paper discusses the evolving classification of NEC, morphological features, and immunophenotypic characteristics that differentiate LCNEC from other neuroendocrine tumours. Survival rates underscore the aggressive nature of colorectal NEC, and treatment options, primarily relying on retrospective studies, reveal limited efficacy. While surgery remains the preferred approach for localized disease, the optimal chemotherapy regimen for LCNEC is yet to be established. Current evidence suggests platinum-based therapy as a common first-line treatment, but the demand for more effective options persists. The paper highlights the need for additional research, including prospective trials, to elucidate the genuine benefits of adjuvant chemotherapy and to explore emerging therapies, such as immunotherapy, in the context of LCNEC.